The effects of carbohydrate supplementation during repeated bouts of prolonged exercise on saliva flow rate and immunoglobulin A - Li, T.-L.; Gleeson, M. (Journal of Sports Sciences, 2005)
The purpose of this study was to assess the effect of carbohydrate (CHO) feeding during different periods of two 90-min cycling bouts (the first bout began at 09:00h and the second bout began at 13:30h) at 60% maximal oxygen uptake (&Vdot;O2max) on saliva flow rate and saliva immunoglobulin A (sIgA) responses to the second exercise bout. The study consisted of three investigations: carbohydrate supplementation during (1) the first hour of the recovery interval (CHO-REC), (2) during the first bout of exercise and (3) during the second bout of exercise. Each investigation included two trials completed in a counterbalanced order and separated by at least 4 days. Participants consumed a lemon-flavoured 10% w/v carbohydrate beverage or placebo (22ml·kg-1 body mass) in the first hour of the recovery interval (n=8) and 500ml just before exercise, followed by 250?ml every 20min during exercise in the first (n=9) and second exercise bouts (n=9). Timed unstimulated saliva samples were collected at 10min before exercise, after 48-50min of exercise and during the last 2?min of exercise, at 1h post exercise, 2h post exercise (first exercise bout only), and 18h post exercise (second exercise bout only). Venous blood samples were taken 5min before exercise and immediately after exercise for both exercise bouts in all trials. The main findings of the present study were as follows. First, carbohydrate ingestion during both exercise bouts, but not during the recovery interval, better maintained plasma glucose concentrations and attenuated the increase in plasma adrenaline and cortisol concentrations after the second exercise bout compared with placebo. Second, carbohydrate feeding had no effect on saliva flow rate and sIgA secretion rate compared with placebo. Third, saliva flow rate and sIgA concentration returned to pre-exercise bout 1 values within 2 h in all trials. Fourth, there was no delayed effect of exercise on oral immunity. These findings suggest that carbohydrate ingestion during the first or second bout of exercise, but not during the recovery interval, is likely to better maintain plasma glucose concentrations and attenuate the responses of plasma stress hormones to a second exercise bout than ingestion of fluid alone. Two bouts of 90 min cycling at 60% &Vdot;O2max on the same day appears to inhibit saliva flow rate during the second exercise bout but does not alter sIgA transcytosis. Our results show that carbohydrate ingestion during any period of two prolonged exercise bouts does not induce different effects on oral immunity compared with placebo.